The 7 habits of highly effective people powerful lessons in personal change - Covey, Stephen R. (Simon & Schuster, 2020)
One of the most inspiring and impactful books ever written, The 7 Habits of Highly Effective People has captivated readers for nearly three decades. It has transformed the lives of presidents and CEOs, educators and parents--millions of people of all ages and occupations. Now, this 30th anniversary edition of the timeless classic commemorates the wisdom of the 7 habits with modern additions from Sean Covey. The 7 habits have become famous and are integrated into everyday thinking by millions and millions of people. Why? Because they work!With Sean Covey's added takeaways on how the habits can be used in our modern age, the wisdom of the 7 habits will be refreshed for a new generation of leaders.